Zoonoses and poverty: The multiple burdens of zoonoses in low- and middle-income countries - Grace, Delia; Cook, Elizabeth A.J. (Springer, 2023)
Poor people have greater exposure to zoonoses through livestock keeping; living in agricultural communities; greater exposure to peri-domestic and wild animals; and less access to clean water and sanitation. Although their consumption of animal source products is low, the quality of these products is poor.